Book Reviews. Issue 3 (1st December 2019) - Belge, Boris; Bara, Anna; Starks, Tricia; Ward, Christopher J.
Abstract : Smoking under the Tsars: A History of Tobacco in Imperial Russia. Tricia Starks. (Ithaca, NY: Cornell University Press, 2018), xiii + 320 pp. ISBN 978-1-5017-2205-9. White Fox and Icy Seas in the Western Arctic: The Fur Trade, Transportation and Change in the Early Twentieth Century. John R. Bockstoce. (New Haven and London: Yale University Press, 2018), 327 pp., index, illustrations, maps, 40.00 (hardback). ISBN 978-0-300-22179-4. Delo—Tabak: Polveka fabriki "Iava" glazami ee rukovoditelia. Leonid Sinel'nikov. (Moscow: Delo, 2017), 511 pp., ISBN: 978-5-7749-1260-5. Life Histories of Etnos Theory in Russia and Beyond. David G. Anderson, Dmitry V. Arzyutov and Sergei S. Alymov, eds. (Cambridge, UK: Open Book Publishers, 2019), 425 pp., https://doi.org/10.11647/OBP.0150, ISBN 9781783745449.